Discrepancies in bone mineral density and fracture risk in patients with type 1 and type 2 diabetes—a meta-analysis - Vestergaard, P. (Osteoporosis international, 2007)
Diabetes affects bone metabolism. The hypothesis was that type 1 (T1D) and type 2 (T2D) affects BMD and fracture risk differently. Pubmed, Embase, and Web of Science were searched using the terms "diabetes", "fracture", and "bone mineral". Hip fracture risk was increased in T1D (RR = 6.94, 95% CI: 3.25-14.78, five studies) and T2D (1.38, 95% CI: 1.25-1.53, eight studies) compared to subjects without diabetes. The increase in relative hip fracture risk was significantly higher in T1D than in T2D. BMD Z-score was decreased in the spine (mean +/- SEM -0.22 +/- 0.01) and hip (-0.37 +/- 0.16) in T1D and increased in the spine (0.41 +/- 0.01) and hip (0.27 +/- 0.01) in T2D. A meta-regression showed that body mass index (BMI) was a major determinant for BMD in both the spine and hip. Glycated haemoglobin (HbA1C) was not linked to BMD. The increase in fracture risk was higher and BMD lower in patients with complications to diabetes. Hip fracture risk is increased in both T1D and T2D, whereas BMD is increased in T2D and decreased in T1D. A common factor such as complications may explain the increase in fracture risk, whereas BMI may ameliorate the increase in fracture risk in T2D.